POSSIBILITIES OF FORECASTING EARLY PREECLAMPSIA IN 11-13 WEEK OF GESTATION - L. D. Belotserkovtseva; L. V. Kovalenko; D. P. Telitsyn (Сибирский научный медицинский журнал)
The purpose of the study was to study the levels of placental growth factor (PlGF) and soluble receptor-1 vascular endothelial growth factor (sVEGF-R1) in the mother’s serum during normal pregnancy and pre-eclampsia developed before 34 weeks of pregnancy in the period 11–13 weeks. Material and methods. In a prospective study, 95 patients were selected on the basis of risk factors for the development of pre-eclampsia in the first prenatal screen and further examined blood for PlGF and sVEGF-R1. According to the results of the course of pregnancy, the patients were divided into 4 groups: the first group – preeclampsia developed before the 34th week of pregnancy, the 2nd group – uncomplicated pregnancy, the 3rd group – pregnancy proceeding with fetoplacental insufficiency, the 4th group – pregnancy ending in preterm labor. Results and discussion. In women with preeclampsia that developed before the 34th week of gestation, the medians of sVEGF and PlGF were 2275 and 64.5 pg/ml, respectively, in pregnancy with placental insufficiency – 648.9 and 31.5 pg/ml, in pregnancy ending in preterm labor – 102.5 and 20 pg/ml, in uncomplicated pregnancy – 1170.0 and 34,5 pg/ml. The results can be used in the screening of the first trimester of pregnancy to predict various pathological conditions of pregnancy.